INFLUENCE OF VEHICLE SUSPENSION PARAMETERS ON ITS BRAKING PROPERTIES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The paper focuses on the study of the performance of elastic and damping parameters of the car suspension. The problem of arising vibrations of the sprung and unsprung vehicle masses on the braking process is considered. The article presents theoretical models of vehicle braking taking into account the oscillations of the vehicle's sprung masses. The research results will make it possible to establish the relationship between the suspension parameters and the estimated parameters of braking properties, to supplement the "driver - car - road" system, and also to more accurately assess the active safety of vehicles associated with braking dynamics.